Prevalensi Kelainan Ginjal Anjing yang Dirawat Rumah Sakit Hewan Pendidikan dan Klinik Hewan Melalui Pemeriksaan Ultrasonografi - Rahmania, Winda; Ulum, Mokhamad Fakhrul; Zaenab, Siti; Noviana, Deni (Jurnal Veteriner; Vol 21 No 2 (2020), 2020)
Kidney disorders frequently occured in dogs and can be examined using ultrasound. The present study was aimed to know the prevalence of abnormalities that occurs in the kidney through ultrasound examination in dogs in the Veterinary Teaching Hospital Faculty of Veterinary Medicine of IPB University and My Vets Animal Clinic Jakarta. Data from 88 dogs were taken and recapitulated based on the results of medical records through ultrasound examination. Data were analyzed descriptively using parameter of body size, age and sex. The results showed the highest prevalence of kidney disease based on body weight occurred in small breed dogs (13.6%) and large breed dogs (11.4%). Based on age the highest prevalence occurred in geriatric dog that was equal to 50%. The prevalence of renal abnormalities by sex was highest in male than female dogs (52.3%). The prevalence of kidney disorder was influenced by body weight, age, and sex. Based on correlation analysis there was a strong correlation between age and sex.